2013
DOI: 10.4067/s0718-16202013000200008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pathogenicity of fungi associated with grapevine trunk diseases in Chilean vineyards

Abstract: Prevalence and pathogenicity of fungi associated with grapevine trunk diseases in Chilean vineyards. Cien. Inv. Agr. 40(2): 327-339. Trunk diseases in grapevine (Vitis vinifera) have been identified as a major problem in the wine and table grape industries around the world, reducing the productivity, quality and longevity of vineyards. The present study examined 694 wood samples from the cordons and trunks of vines with trunk disease symptoms in 67 Chilean vineyards located between Copiapó (27°18' S) and Los A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Roesleriaceae P Root rot Japan Kobayashi (2007) Fungal Diversity Qiu et al (2011), Ú rbez-Torres (2011), Diaz et al (2013), Pitt et al (2013Pitt et al ( , 2015, Li et al (2014), Carlucci et al (2015, Pavlic-Zupanc et al (2015), Valencia et al (2015), Comont et al (2016) Teng (1996) Fungal Diversity …”
Section: Microfungi Collected From China Italy Russia and Thailandmentioning
confidence: 99%
“…Roesleriaceae P Root rot Japan Kobayashi (2007) Fungal Diversity Qiu et al (2011), Ú rbez-Torres (2011), Diaz et al (2013), Pitt et al (2013Pitt et al ( , 2015, Li et al (2014), Carlucci et al (2015, Pavlic-Zupanc et al (2015), Valencia et al (2015), Comont et al (2016) Teng (1996) Fungal Diversity …”
Section: Microfungi Collected From China Italy Russia and Thailandmentioning
confidence: 99%
“…In addition, experiments carried out with axenic plants, trunks and shoots of the Carmenère cv. showed that there were no differences in pathogenicity between D. mutila and D. seriata (Díaz et al, 2013). However, the susceptibility of different wine grape cultivars to D. seriata and D. mutila has not been reported to date.…”
Section: Introductionmentioning
confidence: 97%
“…Fungal species belonging to the Botryosphaeriaceae are responsible for the death of part of the plant, reducing the productivity and profitability of this crop (Gubler et al, 2010). Both D. seriata and D. mutila are associated with the Botryosphaeria die-back in Chile (Díaz et al, 2013;Morales et al, 2012). These fungi have been detected in table grape vineyards where no differences were observed among the Thompson Seedless, Red Globe and Flame Seedless cultivars, which were equally susceptible to infection by D. mutila, D. seriata and Spencermartinsia viticola (Morales et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide economic cost for the replacement of dead grapevine plants has been estimated more than 1.5 billion of dollars per year [1]. However, that cost may be underestimated in view of the individual regional data found in literature, for example nearly 13% of French vineyards are affected by GTDs compared to 22% in Chile [2,3].…”
Section: Introduction mentioning
confidence: 99%